Ritualidades e vida cotidiana na cultura digital: uma investigação sobre os processos de comunicação e ritualização no ciberespaço - Magossi, Priscila Gonçalves (2014)
This research paper discusses the relationships between communication, ritualism and digital culture. Within this broad thematic spectrum, the object of study focuses on the specific boundaries of the organization of daily rituals in cyberspace. Indeed, the theoretical and practical elements of this research call for more careful definitions. According to this analysis, the concept of ritualism refers to a standard of concrete actions undertaken in particular situations for a given purpose. Digital culture, in turn, is marked by postmodern culture, which is characterized by mediatic visibility and organized by a glocal context (i.e., neither local nor global, but rather, a hybrid context with its own magnitude). Sociomediatic processes today are characterized mainly by the logic of excess and fragmentation, by the absence of purpose, and by structural uncertainty. Cyberspace, on the other hand, is seen as a virtual territory where information is transmitted in real time. This territory is comprised of a set of telecommunication networks that are managed by the information digitizing process. Based on these theoretical elements, this research paper addresses the question of how daily rituals are organized in cyberspace. The primary hypothesis is that contemporary humans engage in ritualization on a collective scale, which is developed in cyberspace. It is believed that postmodern times give rise to a group of fragmented rituals that play the role of organizing and instigating ways of thinking in order to create or maintain identities and generate visibility. The objective, therefore, is to understand how the processes of communication and ritualization are established in cyberspace. To this end, the corpus of this research focuses on the social networks Facebook and Twitter. The methodological procedures involve a bibliographic and/or documentary research allied to a critical review of processes, in line with the exclusively theoretical approach of this research (eventual complementary methodological instruments will be defined in a context-oriented analysis). The thematic link between communication, ritualism, digital culture and cyberspace will be established based on the theoretical framework of the theories of communication, postmodernism, media, virtual culture and the imaginary, put forward by authors such as Anderson, Baudrillard, Bauman, Contrera, Eliade, Harvey, Morin, Peirano, Recuero and Trivinho. With these characteristics, this essay intends to contribute to the study of communication and cyberculture, from a necessarily tensional point of view, i.e., more exacting and comprehensive, within the aforementioned thematic field